A study of event-related electrocortical oscillatory dynamics associated with cued motor-response inhibition during performance of the Go/NoGo task within a sample of prenatally alcohol-exposed children and age-matched controls - Gerhold, Mathew Michael (Division of Biomedical Engineering, 2018)
Fetal alcohol spectrum disorders (FASDs) are a spectrum of disorders that occur due to prenatal alcohol exposure (PAE). Response inhibition refers to the ability to inhibit/suppress a prepotent behavioural tendency set in motion during an experimental task. Our research explored neocortical processing in heavy-exposed children from Cape Town, South Africa, performing the Go/NoGo response inhibition task. We utilised event-related electroencephalographic methodologies to examine event-related potentials (ERP) and eventrelated changes in induced oscillatory power - event-related desynchronisation (ERD)/eventrelated synchronisation (ERS). Across visual and auditory Go/NoGo tasks, we observed equivalent levels of inhibitory control between heavy-exposed (HE) participants and normally-developing controls; however, HEs demonstrated significantly slower reaction times relative to the control group. In an auditory ERP study, we observed a number of alcohol-related changes in ERP waveform morphology, such as decreased P2 amplitude, reduced P3 amplitude, and longer P3 peak latency. In addition, within the HE group, late in the trials, a slow-wave component was observed in both experimental conditions. A significant difference in N2 amplitude across conditions that has consistently been observed in normally-developing samples was not observed in the HE group. We extended previous research findings in the visual domain by analysing induced oscillatory responses. We observed within the normally-developing sample: (1) in both experimental conditions, a frontal induced beta-band ERS related to decision-making; and (2) in the NoGo-condition, a frontal gamma-band ERS related to cognitive-control. Within the HE group, the beta-ERS was not observed in either of the experimental conditions, neither was the gamma-ERS observed in the NoGo-condition. Frontal induced beta-power was predictive of performance accuracy in the HE group, but not in the control group. The observed alcohol-related effects were not explained and/or mediated by IQ (WISC-IQ), socio-economic circumstances, comorbid ADHD, or teratogenic effects related to postnatal lead exposure and prenatal cigarette-smoke exposure. Our results point to alterations in scalp-measured event-related neocortical oscillatory dynamics and slower processing of task demands due to heavy PAE. These alcohol-related effects are observable on ERP component measures, primarily related to conflict-monitoring and attention-based processing. PAE also affects induced classes of neocortical oscillatory dynamics related to decision-making and cognitive-control processes required to inhibit a prepotent motor-response.